Learning outcomes in Taiwanese legal general education under english-medium instruction: A mixed-methods structural analysis of language proficiency, language anxiety, and classroom interaction - LYU, JIAYING; Hsueh, An-Chi (Journal of Interdisciplinary Studies in Education, 2026)
Global EMI expansion has transformed higher education, but evidence for its impact in legal general education is scarce. In Taiwan, under the 2030 Bilingual Nation policy, this mixed‐methods study surveyed 812 undergraduates at twelve universities and conducted interviews with classroom observations. Structural equation modeling showed that English proficiency enhances learning outcomes both directly and indirectly by reducing language anxiety. High levels of course interaction neutralize the negative effect of anxiety on outcomes in interactive settings. The model explains 55 percent of variance in learning outcomes and remains robust after controlling for gender, socioeconomic status, and region. Qualitative findings identify peer support and immediate instructor feedback as key buffering mechanisms.